Efficacy of terbinafine and itraconazole on a experimental model of systemic sporotrichosis Eficiência de terbinafina e itraconazol em um modelo experimental de esporotricose sistêmica - Ana Raquel Mano Meinerz (Brazilian Journal of Microbiology, 2008)
Itraconazole is currently considered the drug of choice to treat the diverse clinical presentation of sporotrichosis. On the other hand terbinafine by virtue of its excellent in vitro activity is under comparative evaluation for its therapeutic potential for a wide range of fungal infections. In this study, our aim was to determine the in vivo efficacy of terbinafine and itraconazole on a experimental model of systemic sporotrichosis. 120 rats Wistar received an injection of 2x10³ S. schenckii cells by via the lateral tail vein. After 3 days the animals were treated with terbinafine (250mg/kg) and itraconazole (100 mg/kg) and their respective diluents. In our model, terbinafine and itraconazole were effective in reducing the number of clinical lesions and positive organ cultures. There was statistical difference between the groups treated with the antifungals in relation to the control groups (p<0,05) concerning the clinical alterations, anatomic-pathological findings and in the positive organ cultures of the agent, being that the treated animals resulted in the absence and/or reduction of all the evaluated parameters. As for the treatments, terbinafine showed similar or higher activity that itraconazole in the evaluation of the testicle alteration (p=0,0004), as well as in the positive organ cultures of microorganism from the organ (p=0,0142). With these results it is possible to conclude that the antifungals studied are effective in the treatment of experimental systemic sporotrichosis. Itraconazol é atualmente considerado a droga de escolha para o tratamento das diferentes formas clínicas da esporotricose. Por outro lado a terbinafina devido a sua excelente atividade in vitro está sendo avaliada quanto ao seu potencial terapêutico frente a diversas infecções fúngicas. O objetivo deste estudo foi determinar a eficácia in vivo da terbinafina e itraconazol em um modelo de esporotricose experimental sistêmica. 120 ratos Wistar receberam uma injeção de 2x10³ células de S. schenckii pela veia lateral da cauda. Após 3 dias os animais foram tratados com terbinafina (250mg/kg) e itraconazol (100mg/kg) e os seus respectivos diluentes. No modelo experimental estudado, a terbinafina e itraconazol se mostraram efetivos reduzindo o número de sintomas clínicos e retroisolamento positivo para o agente. Houve diferenças estatísticas entre os grupos tratados com os antifúngicos em relação aos grupos controle (p<0,05) nas alterações clínicas, achados anatomopatológicos e no retroisolamento do agente, sendo que os animais tratados resultaram na ausência e/ou diminuição de todos os parâmetros avaliados. Quanto aos tratamentos a terbinafina se mostrou com atividade similar ou superior ao itraconazol quando avaliado as alterações anatomopatológicos do testículo (p=0,0004), assim como no retoisolamento do órgão (p=0,0142). Com estes resultados permite-se concluir que os antifúngicos estudados são efetivos no tratamento da esporotricose sistêmica experimental.